Benefit analysis of regional energy interconnection using system dynamics method targeting carbon neutrality - Lv, Ming; Gao, Zijing; Jiang, Han; Gao, Yi; Gao, Yuan (Frontiers in Physics, 2025)
The construction of the global energy internet is a significant way to develop clean energy and the key to achieving the goal of carbon neutrality. This study aims to the feasibility of trans-national and trans-continental development of energy interconnection. The trend of regional power grid interconnection is accelerating, and the influence of energy interconnection on global economic and social development is increasing. The prior literature is absent on technical issues such as energy transmission, storage, sharing, and system issues such as power trading, overall architecture, and data collection. This paper presents the contribution of an utterly systematic model and method for evaluating the comprehensive benefits of energy interconnection and analyzes the comprehensive benefits of energy interconnection development from multiple dimensions in economics, society, resources, and links. This paper takes the economic and clean energy development system in Southeast Asia as an example to make the system simulation, designs scenarios of quick, steady and slow carbon peaking & neutrality, and evaluates the comprehensive benefits under the three economic development modes using the evaluation model. The result presented that the development of energy interconnection has an apparent positive effect on economic growth, eliminating the people lacking electricity, poverty, and other social problems, improving resource utilization efficiency, and the ecological environment. The method proposed in this paper for evaluating the benefits of solving energy interconnection issues is practical and feasible and offers adaptable policy insights for regions at different development.